Characteristics of Procalcitonin Values and Absolute Neutrophil-Lymphocyte Ratio in Pneumonia Sepsis Patients in the Intensive Care Unit of a Hospital H. Adam Malik - Angela Yurika Purba; Syamsul Bihar; Bintang YM Sinaga (International Journal of Health and Pharmaceutical (IJHP), 2026)
.Sepsis pneumonia ranks among leading causes of global mortality, particularly in ICU settings, yet local biomarker profiles remain underexplored in resource-limited contexts like Indonesia. This study aimed to characterize procalcitonin (PCT) and absolute neutrophil-lymphocyte ratio (NLR) in ICU sepsis pneumonia patients at RSUP H. Adam Malik Medan (2023). Employing an observational analytic cross-sectional design, total sampling captured 132 patients meeting Sepsis-3 criteria (qSOFA ≥2, SOFA ≥2, age ≥18 years) with complete PCT/NLR data. Secondary data from medical records were analyzed using SPSS 25 via univariate descriptives and Spearman bivariate tests. Results revealed demographic dominance of males (61.37%) and age ≥60 years (40.15%), lymphopenia (94.70%), neutrophilia (90.90%), critical NLR (>17; 50%), and PCT predominantly in sepsis/infection range (0.5-2 ng/mL; 39.39%) followed by septic shock (>10 ng/mL; 29.55%). In conclusion, elevated NLR and PCT confirm severe inflammation patterns aligned with Sepsis-3, supporting biomarker-guided therapy to mitigate antibiotic overuse in Indonesian ICUs.